Legal Certainty in the Mediation of Islamic Economic Cases: A Critical Analysis of Procedural Law and Its Reconstruction Efforts in Religious Courts - Khairani Harahap, Sarah; Rahmat Hidayat, Wildan; Arif Khoirudin, Akhmad (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Legal certainty of mediation results in sharia economic cases in the Religious Courts is an important issue in the context of modern dispute resolution that prioritizes substantive justice and the efficiency of the legal process. Although mediation is intended as an alternative means of win-win solution, there is still debate about the extent to which the peace certificate resulting from mediation is able to provide a guarantee of legal certainty equivalent to a judge's decision. This research aims to analyze mediation procedures in sharia economic disputes and assess the legal certainty of peace deeds as a guarantee of legal certainty for the parties. This research uses normative juridical research that focuses on written legal norms, namely laws and regulations, court decisions, legal theories, and doctrines of jurists. The results showed that mediation procedures have been systematically regulated in PERMA Number 1 of 2016 which is substantially in accordance with the culture of Indonesian society which prioritizes deliberation in problem solving. The mediation agreement outlined in the peace deed has permanent legal force and can be executed like a judge's decision. Moreover, the peace deed resulting from mediation even more guarantees legal certainty, because it cannot be appealed in accordance with Article 130 HIR. Legal certainty born from the results of mediation not only reflects the clarity of the legal position of the parties, but also guarantees the protection of disputed rights in a fair and peaceful manner. This is in line with Jasser Auda's contemporary maqashid theory which emphasizes the importance of purposefulness and interrelated hierarchy. The deed of peace resulting from mediation authorized by the judge has permanent legal force and provides legal certainty, expediency, and justice as the theory of Gustav Radbruch. Thus, mediation has the potential to be an ideal settlement mechanism in sharia economic cases if supported by an effective and responsive legal system.